The Occurrence of Metabolic Syndrome In Patients With Psoriasis - Musarrat Hussain Raza; Nadia Iftikhar; Asher Ahmed Mashhood; Muhammad Ammar Bin Hamid; Shahan Tariq; Farhat Rehman (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine occurrence of metabolic syndrome in patients of Psoriasis and to highlight any gender-based differences.Study Design: Cross-sectional study design.Place and Duration of Study: Pak-Emirates Military Hospital, Rawalpindi. Our research was conducted from July to December 2020 (6 months).Patients and Methods: A total of 80 patients diagnosed with psoriasis were selected using non-probability consecutive sampling. Informed written consent was obtained from each patient and a questionnaire was filled. Variables such as blood pressure, waist circumference, body surface area covered by psoriasis, and Psoriasis Area Severity Index were recorded on initial visit. Fasting blood sugar, serum triglyceride and HDL cholesterol levels were advised. Patients were diagnosed to have metabolic syndrome if 3 or more of the 5 criteria for the modified version of the National Cholesterol Education Program Adult Panel III were met.Results: There were 62 male & 18 female patients. A total of 39 patients (48.8%) met the criteria for metabolic syndrome. Amongst these, 26/62(41.9%) males & 13/18(72.2%) females fulfilled the criteria. The mean BMI of males was 26.0 and those of females was 28.3 & their comparison demonstrated a noteworthy difference (p=0.04). A statistically significant (p=0.038) positive correlation (r) of 0.233 was observed between body surface area and BMI.Conclusion: Metabolic syndrome is seen frequently in patients of Psoriasis. Female patients have a significant frequency of metabolic syndrome and tend to have a higher BMI than males.